Quantitative MRI Evaluation of Coracohumeral Ligament and Inferior Glenohumeral Capsule Thickening in Adhesive Capsulitis: Correlation with Range of Motion and Edema Patterns - Karaagac, Seda Sogukpinar; Yesilmen, Nevzat (Aves, 2026)
Background: Adhesive capsulitis involves capsular fibrosis and restricted shoulder movements, particularly external rotation and abduction. Magnetic resonance imaging (MRI) enables assessment of capsular and ligamentous thickening. The relationship between capsular thickness, range of motion (ROM), and rotator cuff and biceps tendon pathologies remains unclear. This study aimed to investigate the relationship between the coracohumeral ligament and inferior glenohumeral capsule thickness, shoulder range of motion, and MRI-detected edema patterns in patients with adhesive capsulitis. Methods: This prospective study included 100 adhesive capsulitis patients who underwent shoulder MRI between July 2024 and July 2025. Coracohumeral ligament (CHL) and inferior glenohumeral capsule (IGHC) thicknesses were measured, and rotator cuff and biceps tendon pathologies graded. Shoulder ROM in external rotation (ER) and abduction was measured using a goniometer. Analyses included correlation tests, multiple linear regression, and Kruskal-Wallis tests. Results: The mean patient age was 57.7 +/- 11.9 years, with 66% women. CHL thickness strongly negatively correlated with ER ROM (r = -0.82, P < .001), while IGHC thickness strongly negatively correlated with abduction ROM (r = -0.79, P < .001). Regression analysis showed that CHL thickness independently predicted ER limitation, and IGHC thickness predicted abduction limitation. Rotator cuff and biceps tendon pathologies were common but not independently associated with ROM. Conclusion: Coracohumeral ligament and IGHC thickening are key determinants of restricted shoulder mobility in adhesive capsulitis. Magnetic resonance imaging assessment of these structures provides reliable diagnostic markers and can guide treatment, while concomitant rotator cuff and biceps pathologies have a limited impact on ROM restriction.
Keywords: Adhesive capsulitis; ligaments; magnetic resonance imaging; physical; radiology; range of motion; shoulder joint